Urgensi Pendidikan Karakter di Perguruan Tinggi - Rumapea, Murni Eva (Universitas Negeri Medan, 2015)
The higher education bears great responsibility and obligation, especially to develop intelectual human resources who can be contribute to state and nation such as in the fields of politic, law, economy, education, health, religion, and others for elevating quality of life and wealth of society. However young generation today, performs lower quality in moral and character, so that the higher education must improve the studentsâ morality and character along with all of its âcivitas academicaâ. Educating character in the higher education purposes to anticipate degradation of character, and also serve to forms the hardy character of students for facing toward the various of challanges. By educating character the students become nationâs young intelectual who have prime pesonality as the goals of national education. The implementation of educating charater in the higher education should be teach the accentuate on the cognitive matter, but also on the affective, conative, and skilled matter. The important thing which should be noticed that learning character must be applied on all of the subject matter, so that, all the lectures and collegeâs employees pay attention to our nation and state.